Learning through learners: Indonesian EFL Learners’ Writing Strategies Experiences - Ira Yuliani; Fahrus Zaman Fadhly (Universitas Kuningan, 2020)
This research focuses on writing strategies of EFL learners in writing English text. It attempted to address the following problems i.e. the most frequent writing strategies used and the differences writing strategies used by male and female students. The data collected from questionnaires and interview were analyzed qualitatively based on Oxford (1990) language learning theories. It was found that there were six categories of writing strategies used by the students in English text; memory strategies, cognitive strategies, compensations strategies, metacognitive strategies, affective strategies and social strategies. The result revealed that compensation strategies (18,7%) were the most frequent strategies used by both male and female students in writing English text. It was also found that the female respondents used more varied writing strategies (70,9%) compared to the male ones but the male students was the highest user of affective strategies (66,2%). As the final points, the compensations strategies seem as the best help strategies used in writing English text that can overcome students’ limitation and the use of writing strategies depend on the students’ choice. Hopefully, the next researchers who are interested in observing writing strategies can explore deeper and wider, especially in writing specific genre.